Mass identity architecture : architectural writings of jean baudrillard - Proto, Francesco ([S.l.] : Academy Press, 2006)
This new edition further explores the connection between the cultural analysis provided by the contemporary philosopher Jean Baudrillard and the new 'star' of global culture - architecture. In a world in which images have become a substitute for reality - i.e. simulacra capable of both stimulating and satisfying collective needs - the question arises as to whether architecture could be seen as a 'super-fetish', capable of both mirroring and shaping western society's culture and identity. The aim of this book is thus to provide new methodologies and to suggest new meanings for the comprehension and development of contemporary architecture. In Baudrillard's terms, architecture could be seen as the supreme medium of contemporary visual culture, especially in its potential to influence the individual's perception of reality as a component of the mass-media system. This kind of cultural analysis of the built environment and its effect on everyday life is still a relatively new phenomenon - both in the fields of critical theory and even more so in mainstream architectural criticism. This book, which forms a significant resource on the work of an immensely important writer, should appeal to a wide range of readers. Through highly evocative writing, it provides a theoretical, illuminating pathway for everyone who, either directly or indirectly, is involved or interested in architecture, urbanism and related subjects.
Keywords: Aesthetics; Architecture and society; Architecture, Modern; Architecture, Modern--Philosophy; Architecture--Aesthetics; Baudrillard, Jean, 1929-2007